Estimation of girth of humeral head by measuring the biepicondylar distance: A validity and reliability study (Annals of Medical Research, 2024)
Aim: The aim of this study was to estimate the girth of humeral head (GOHead) by analysing the reliability and validity of biepicondylar distance (BED).Materials and Methods: The study was carried out on 66 dry humeruses (36 right and 30 left) at the Ondokuz Mayıs, Ordu and Erciyes Universities, Faculty of Medicine, Departments of Anatomy. The BED and the GOHead were measured, and the related ratio was determined. The validity between the obtained values was analysed by Bland Altman analysis and the reliability by intraclass correlation coefficient (ICC).Results: The BED was measured to be 57.70±5.18 mm, while the GOHead was 132.77±12.17 mm. The relative ratio between the two data was determined to be (RR:2.30). The GOHeadRR (BED x RR) value was defined to be 132.82±12.01 mm. While the results of this study showed agreement in validity according to Bland Altman analysis, an excellent reliability ratio (Cronbach Alpha's: 0.930) was determined in this study.  Estimation of the GOHead using the formula (BED x 2.30) shows agreement in terms of validity and reliability.Conclusion: This result we obtained shows that the BED can be used to estimate the GOHead without requiring any imaging method. Based on the results of this study, it is expected to play an important role in reducing the use of radiological materials in GOHead measurements and reducing the radiological footprint.
Keywords: Humerus; Humeral head; Epicondyle; Biepicondylar distance